2008
DOI: 10.1620/tjem.216.267
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin Receptor Blockade with Tezosentan Ameliorates Myocardial Injury Induced by Abdominal Aortic Ischemia-Reperfusion

Abstract: Endothelin is both a potent vasoconstrictor and an important mediator of ischemia-reperfusion (IR) injury. Therefore, the role of endothelin receptor antagonism in IR-inducedtissue injury carries great interest. Here, we examined the effect of tezosentan, a nonselective antagonist for endothelin receptors, on myocardial injury induced by abdominal aortic IR, which represents a model of the IR injury in distant organs frequently occurred after vascular surgery. Thirty-two Wistar rats were randomized into four g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Kiris et al 7 found significant increases in the levels of malonydialdehyde, catalase and superoxide dismutase and myeloperoxidase activity in rats in the aortic I/R group in which 60 minutes of reperfusion was applied after a 30-minute ischemia compared to the control group. Narin et al 9 found significant increases in the levels of malonydialdehyde, catalase and superoxide dismutase and myeloperoxidase activity in rats in the aortic I/R group in which 120 minutes of reperfusion was applied after a 120-minute ischemia compared to the control group. We applied 120 minutes of ischemia followed by a 120 minutes of reperfusion in the study groups of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Kiris et al 7 found significant increases in the levels of malonydialdehyde, catalase and superoxide dismutase and myeloperoxidase activity in rats in the aortic I/R group in which 60 minutes of reperfusion was applied after a 30-minute ischemia compared to the control group. Narin et al 9 found significant increases in the levels of malonydialdehyde, catalase and superoxide dismutase and myeloperoxidase activity in rats in the aortic I/R group in which 120 minutes of reperfusion was applied after a 120-minute ischemia compared to the control group. We applied 120 minutes of ischemia followed by a 120 minutes of reperfusion in the study groups of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogen peroxide, hydroxyl and superoxide radicals, the main reactive oxygen products, are shown to result in peroxidation in membrane phospholipids of myocardial tissues cells [ 4 ] . In addition, I/R injury is suggested to increase by remote organ infiltration of activated neutrophils due to aortic I/R and the myeloperoxidase enzyme released by them [ 4 , 18 , 19 ] . Moreover, released cytokines, particularly tumor necrosis factor-, induce leukocyte activation and also damage capillary continuity [ 17 ] .…”
Section: Discussionmentioning
confidence: 99%
“…As understood, distant organ I/R injury is not a single reaction, but rather a complex process with intracellular and extracellular pathophysiologic changes. Histological changes in the heart, resulting from I/R, can be seen via the light microscope [ 19 ] . Variables such as myofibrillar edema and focal hemorrhage detected under the light microscope were recorded in the I/R group, but not in the control group, which is suggested to be an indicator of distant organ I/R injury in the heart due to abdominal aorta operation.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, tezosentan, a dual receptor antagonist, given on the first day after MI increased long term survival and improved hemodynamic conditions [107]. It was also shown to have protective effects on myocardial injury induced by ischemia-reperfusion [121]. Even a selcective ET-A receptor blocker in acute setting has been documented to be superior to chronic blockade in attenuating ischemia/reperfusion injury in failing hearts [122].…”
Section: Animal Experimentsmentioning
confidence: 99%